The Opportunity to Establish an Extradition Mechanism in the ASEAN - Muhammad Ryan Ramadhani Miano; Rachminawati Rachminawati (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2023)
Extradition is transporting a suspect or defendant to the nation where the crime was committed to be prosecuted and punished. Under international law, states are not required to enter into extradition agreements. There are impediments to the implementation of extradition, such as disparities in sovereignty principles and perspectives on offenses; in addition, this impediment exists at the regional ASEAN level, such as terrorism that can be extradited based on the UN Convention, even without an agreement, recognizing its impact on sovereignty. Therefore, the conclusion of an extradition agreement is crucial. Using normative research methodologies and legal perspectives, this study will explore the prospects and challenges in forging extradition agreements at the ASEAN regional level and compare them to the E.U. processes. The study's results indicate that there is still enormous potential for forming an ASEAN extradition treaty, which has made substantial progress with the 2018 provisional draught. Regional barriers and limits comparable to those encountered by ASEAN are anticipated. Therefore, an extradition convention will assist law enforcement and contribute to regional collaboration. With an extradition agreement, perpetrators can be punished by the proper state, and victims or society can be restored to justice.